SISTEM INFORMASI PENGELOLAAN ASET BARANG MILIK NEGARA (BMN) PADA IAIN KUDUS BERBASIS ANDROID - Fauzi, Sa'ad; Latifah, Noor; Muzid, Syafiul (Antivirus : Jurnal Ilmiah Teknik Informatika, 2025)
The management of State-Owned Assets (BMN) at the State Islamic Institute (IAIN) Kudus still faces various challenges, such as difficulties in asset tracking, lengthy distribution processes, and limited access for work units. This study aims to design and develop an Android-based BMN Asset Management Information System to accommodate the internal needs of IAIN Kudus. The system development method used is Rapid Application Development (RAD) with PHP and Kotlin programming languages and MySQL database. The system is designed to provide various features, such as inter-unit asset transfer, QR Code-based asset tracking, multilevel user access, asset borrowing, asset history, and Android-based notifications. Testing results indicate that the system effectively enhances the efficiency and accountability of BMN asset management at IAIN Kudus.